Pragmatist Politics : Making the Case for Liberal Democracy. - McGowan, John (Book collections on Project MUSE., 2012)
In our current age of cynicism, John McGowan suggests that the time is right to take a fresh look at pragmatism, the philosophy of American democracy. As McGowan shows, pragmatism can be an inspiring alternative to the despair that seems to dominate contemporary American politics. Pragmatist Politics is passionate and convincing, both heartfelt and clear-eyed. It offers an expansive vision of what the United States could be and should be. From John Dewey and William James, McGowan derives a history of democracy as a way of life, characterized by a distinctive ethos and based on an understanding.